GERAKAN LITERASI DI KELAS V MIN I YOGYAKARTA - Fajriati Dwi Lestari (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
Reading is one of the activities that is often carried out during learning, but the reality seen by researchers is that reading levels in elementary schools are still low. Therefore, literacy activities including reading need to be familiarized to children from an early age. MIN I Yogyakarta as one of the superior madrasahs familiarizes children with reading through the literacy movement. Data was collected through observation, interviews and documentation. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) the types of literacy found in class V MIN I Yogyakarta include basic literacy, science literacy, library literacy, and technology literacy. (2) strategies implemented by reading 15 minutes before learning begins, there is a reading corner in each class with students bringing books from home to school so that students can read whenever and wherever, the literacy movement is integrated with the 2013 curriculum, writing down the essence of reading or making a synopsis, discussions and presentations, procurement of library materials. (3) the impact caused by the literacy movement such as students showing a penchant for writing, increasing the number of visits to the library, creating a literate environment by getting used to reading, easing the teacher's burden in training students' ability to obtain information with high curiosity so that students have broad and deep knowledge and insight.